An efficiency analysis of food distribution system through data envelopment analysis. (7th December 2019) - Paciarotti, Claudia; Bevilacqua, Maurizio; Ciarapica, Filippo Emanuele; Mazzuto, Giovanni; Postacchini, Leonardo
The specific quality and safety requirements, typical of the food supply chain, force to strong action on implementing distribution networks, reducing transport and delivery costs, improving distribution efficiency and performance, increasing carriers control and flexibility. In this context, the selection and evaluation of third-party logistics has become a crucial aspect in order to realise an efficient food products distribution, with both a high level of service and competitive costs. This paper implements data envelopment analysis theory to analyse the case of an Italian food producer, which distributes its products on the national territory, through several third-party logistic carriers. This study made possible to define the most efficient carrier among those responsible for the distribution process, analysing the retail trade and large-scale retail trade. This paper represents a reference guideline to all the food companies involved in the process of evaluation and improvement of the distribution process.